A novel arch lattice-shell of enlarged cross-section hoods for micro-pressure wave mitigation at exit of maglev tunnels. (February 2023) - Zhang, Jie; Wang, Yuge; Han, Shuai; Wang, Fan; Gao, Guangjun
Graphical abstract: Highlights: The high-speed maglev train/tunnel coupling aerodynamic characteristics has been studied. A novel arch lattice-shell of enlarged cross-section hoods has been proposed. Propagation and evolution properties of initial compression waves have been clearly illustrated. The mitigation mechanism of the arch lattice-shell has been revealed. Abstract: With technology development of 600 km/h high-speed maglev trains, how to effectively alleviate the transient pressure wave problem caused by such a high-speed maglev train passing through the tunnel is significantly of importance. In this paper, based on the three-dimensional, unsteady, compressible Navier-Stokes equations and k-epsilon turbulence model, a high-speed maglev train with a speed of 600 km/h was simulated to pass through a single-track tunnel with a cross-sectional area of 92 m 2, and the numerical method used was validated by a moving model test. The propagation characteristics of pressure waves in the tunnel and the evolution properties of the initial compression wave were explored. A new enlarged cross-section hood with an arch lattice-shell was proposed. With helps of the semi-closed decompression domain formed by the outer wall of the inner arched plate and the inner wall of the enlarged cross-section tunnel hood, the novel hood can further dissipate the energy of the initial compression wave; thus, the pressure gradient at 140 m from the tunnel entrance and the micro-pressure wave amplitude at 20 m from the tunnel exit can reduce by 32.1 % and 35.6 % respectively, as compared with the existing enlarged cross-section tunnel hood. When compared to the tunnel without hoods, this novel hood can achieve 64.8 % and 74.3 % reduction at the same monitoring points.